Chapter Un'anonima relazione delle piramidi d'Egitto del 1743. Appunti preliminari in vista dell'edizione critica del ms. α. G. 5. 27 (BEUMo) - Bellucci, Nikola D. (Studi e saggi, 2021)
This paper provides news of the rediscovery of a new Travel Report in Egypt (with a description of the Pyramids) dated 1743. In view of the critical edition of the document, will be deepened the context of the re-discovery, attempting to outline preliminary investigative ways.